The Role of Citizenship Education in Building Democracy in Indonesia - Rohali, Alya (International Journal of Students Education, 2024)
Civic education is an integral part of the education system. Civic education is not something new in the context of Indonesian education. There have been many changes made both in context and terms by the Indonesian Government to realize its mission in building democratic education. Civic Education is an education that reminds us of the importance of the values of the rights and obligations of citizens so that everything is in accordance with the ideals of the nation. The meaning of democracy in Indonesia has not been fully realized, this can be seen from the many conflicts that occur because of a sense of freedom towards something fundamental, such as the right to obtain and provide information. Therefore, the process of Civic Education needs to be realized in the curriculum and learning at all levels of education. This study uses a literature analysis method with grounded theory, namely a qualitative research method that uses a number of systematic procedures to develop a theory that is compiled inductively. The basic theory of research, the inductive research technique of this study, emphasizes observation and develops the basis for the practice of "intuitive" relationships between variables. Education as one of the government's strategies in building a democratic generation with the implementation of models and materials for learning Civic Education. Learning democracy in the study of state constitutional material, learning the obligations and rights of citizens.